Очерк теории развития буржуазной политэкономии - Волков Юрий Владимирович (Издательство ЛГУ, 1988)
Экземпляры: КХ (20150328) / Инвентарный номер: 913385 / Цена: 1.50 / Сис.шифр: 33 / Авт.знак: В 67 / ГРНТИ: 06 / ББК: 65